PENERAPAN POMPA HYDRAM PARAREL UNTUK MENGATASI PERMASALAHAN AIR BERSIH DI DESA KESIMPAR-KARANGASEM - IGN. Putu Tenaya; IGK Sukadana; IKG. Wirawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2016)
Kesimpar village located in the district Abang, regency of Karangasem. Consists of 2750 inhabitants, ofwhich 95 percent are farmers and ranchers. To meet the water needs from Andong water resources hascapacity 10 liters per second, with a walk takes 2-3 hours. From the initial survei and mapping of thesituation by the team, accompanied by community leaders, it is possible to build clean water sistems withapplication technologist hydram pump. Tim from Mechanical Engineering of Udayana University ready tohelp designing and assisting in building the sistem. The target of this service are: the establishment of waterservices, distribution evenly to every community with the appropriate discharge national standards. Resultingfrom the implementation of activities: Village Kesimpar clean water source that has the potential to be fullyutilized. It was decided to use hydram pump valve tap spherical models, the dimensions of the pump: pumpbody diameter 6 inch, 8 inch diameter of air tube, diameter/length drive pipe 6 inch/54 m. The execution ofthe planned sistem is evidenced by pumping beats period 40-44 perminute. Evaluation of the pumpingcapacity has reached capacity planning, one pump has a capacity of 0.9 - 1.0 liters/minute, and two pumpsare installed in parallel has a total capacity of 1.8 - 2.0 liters/min. Residents in the area Pura Bangun Saktisome 50 families had served with clean water.